Depression among Patients with Multi Drug Resistance Tuberculosis - Debi Ariyanto; Muchlis Achsan Udji Sofro; Meidiana Dwidayani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Patients with Multi Drug Resistance Tuberculosis (MDR-TB) during treatment can influence problems psycological conditions such as depression. The purpose of this study was to identify the determinants of depression condition in patients with MDR-TB in outpatients clinic. A cross-sectional study was conducted involving 47 patients. Subjects were selected through consecutive sampling methods. Instrument used in this study were Beck Depression Inventory (BDI-II) which consists of 21 items. Each items a scored form 0 (not) to 3 (severe). Demographic data observed consist of age, gender, education level, profession, length of treatment, funding, region and regimen therapy. Data were analyzed using chi square testing. The level of significance used for the statistical test was p < 0,005. MDR TB patients’ characteristics showed there were more males (53.02%), age 41 - 60 years (51.1%), senior high school (40,4%), permanent works (48,6%), more than 12 months on treatment (44,7%), funding by goverment health inssurance (61,7%), living in cities (72,3%) and had individual regimen therapy (91,4%). Proportion of depressive among the subjects was 27,7%. The analysis showed there was only gender had association with depression in MDR TB patients ( p value 0.01). Depressive were found in subjects with MDR-TB during treatment. The variables of age, education level, profession, length of treatment, funding, region and regimen therapy was no significant association with depressive condition.